Cross-domain multi-copy of flow discovery mechanism based on dual certificate storage - Haiyang LUO; Bin KUANG; Shoukun GUO; Lingcui ZHANG; Ben NIU; Fenghua LI (Tongxin xuebao)
To solve the problems of the privacy information leakage caused by the deliberate or inadvertent retention of information when information was frequently exchanged across nodes and systems in a ubiquitous sharing environment, a cross-domain multi-copy of flow discovery mechanism based on dual certificate storage was proposed, which could trace the propagation path and channel, and construct a multi-copy propagation graph of the information.Depending on the timing and method of certification, the dual certification was comprised active circulation certification and passive operation certification.Before the information was shared, the information sharer actively recorded the propagation path and method to generate active circulation certification records.Before the information was operated, the system automatically recorded the propagation path to generate passive operational certification records.Compared with single certificate storage, the dual certificate storage could improve the integrity and authenticity of the constructed multi-copy propagation graph of information, and could detect nodes with abnormal certificate storage behavior and provide disposals.Based on the theory of social punishment, the effectiveness of abnormal certificate storage behavior detection and handling was demonstrated.A prototype system for multi-copy discovery of OFD with dual certificate storage is developed, the improvement of information dissemination graph construction integrity by the proposed mechanism is verified.